2001
DOI: 10.1021/bi002326q
|View full text |Cite
|
Sign up to set email alerts
|

Trapping Conformational Intermediate States in the Reaction Center Protein from Photosynthetic Bacteria

Abstract: In protein, conformational changes are often crucial for function but not easy to observe. Two functionally relevant conformational intermediate states of photosynthetic reaction center protein (RCs) are trapped and characterized at low temperature. RCs frozen in the dark do not allow electron transfer from the reduced primary quinone, Q A -, to the secondary quinone, Q B . In contrast, RCs frozen under illumination in the product (P + Q A Q B -) state, with the oxidized electron donor, P + , and reduced Q B -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
109
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(128 citation statements)
references
References 62 publications
(127 reference statements)
18
109
1
Order By: Relevance
“…Similar long lived states have been observed by other authors for native RCs frozen under different illumination conditions (15,18,38,41,42). In principal the longer lifetime of the long lived state frozen in the light may be due to a reduced electron transfer rate for the back electron transfer reaction.…”
Section: Effects Of Protein Response On Functional Properties Of Q Bsupporting
confidence: 85%
See 2 more Smart Citations
“…Similar long lived states have been observed by other authors for native RCs frozen under different illumination conditions (15,18,38,41,42). In principal the longer lifetime of the long lived state frozen in the light may be due to a reduced electron transfer rate for the back electron transfer reaction.…”
Section: Effects Of Protein Response On Functional Properties Of Q Bsupporting
confidence: 85%
“…In early studies, large differences in transfer rates were observed between RCs frozen in the light or in the dark (14,15,18). For RCs frozen in the dark and illuminated at cryogenic temperatures, the reaction k AB…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, electron transfer rates were measured for RCs frozen in different states at cryogenic temperature (5,43,63,64). s with a fraction that did not recover, attributed to samples that may have lost the electron on the acceptor side.…”
Section: Electron Transfer Rates Of Rc In Different Conformational Stmentioning
confidence: 99%
“…Subsequently several studies to investigate these conformers (i.e. substates) were performed and the properties of charge separation investigated (43,73). These states have been proposed in a general sense to differ in the detailed interactions between Q B and the protein.…”
Section: Conformational Gatementioning
confidence: 99%